The association of soluble cluster of differentiation 36 with metabolic diseases: A potential biomarker and therapeutic target - Yun Li; Yaxi Chen; Xiong Z. Ruan (Wiley, 2023)
Abstract A cluster of differentiation 36 (CD36), also known as fatty acid translocase, plays an important role in developing and progressing metabolic diseases. Soluble CD36 (sCD36), a circulating form of CD36, is identified in human plasma. Current studies have demonstrated that sCD36 is an early biomarker of type 2 diabetes (T2DM) and atherosclerosis risk and may act as a key molecule in organ cross‐talks directly or indirectly. This review summarizes the cell sources, molecular structure, potential production mechanism, functions, and regulators of sCD36. We highlight the association of sCD36 with hyperlipidemia, metabolic inflammation, T2DM, cardiovascular disease, non‐alcoholic fatty liver disease, diabetic kidney disease, and obesity. These studies suggest that sCD36 could be a useful biomarker for metabolic diseases in children and a potential therapeutic target in preventing metabolic diseases.